Hermeneutika Hukum: Prinsip dan Kaidah Interpretasi Hukum - Weruin, Urbanus Ura; Andayani B, Dwi; Atalim, St. (Mahkamah Konstitusi Republik Indonesia, 2016)
This legal hermeneutic article efforts to explore and formulates norms, rules, principles, standards, and criterions that must be referenced in order to understand, analyze, interpret, and explicate the intention and complexities meaning of legal texts, not only according to literary meaning but also to reveal the whole meaning of pratices and outcome of the legal adjudication. These norms, rules, and principles link to primary or general priciples, attitudes and goodwill of intepreter, aim of interpretation, interest of people, structure of legal system, character and role of interpreter, and how to undestand and treate legal noms as text. This bibliographical study and empiris research article find out the meaning, history, and aplication of legal hermeneutic in practices of adjudication. One case from legal adjudication (court dicision) will be analysed here according to principles of legal hermeneutic.